2006
DOI: 10.1136/ard.2005.035378
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with rheumatoid arthritis is associated with a reduced number and impaired function of endothelial progenitor cells

Abstract: Endothelial dysfunction in patients with RA with low grade inflammation is associated with a reduced number and partial dysfunction of EPC. Further studies are needed to explore whether interventions that potentially ameliorate the number and function of EPC also improve endothelial function in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 23 publications
9
133
1
7
Order By: Relevance
“…In contrast to the above-mentioned observations of elevated circulating EPC levels in mouse arthritis models, studies in humans have shown that EPCs are decreased in the peripheral blood of patients with active RA compared with healthy individuals (21,22). Depletion of EPCs from the circulation in RA patients with established disease reflects their enhanced extravasation out of the bloodstream and into the inflamed joint.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to the above-mentioned observations of elevated circulating EPC levels in mouse arthritis models, studies in humans have shown that EPCs are decreased in the peripheral blood of patients with active RA compared with healthy individuals (21,22). Depletion of EPCs from the circulation in RA patients with established disease reflects their enhanced extravasation out of the bloodstream and into the inflamed joint.…”
Section: Discussionmentioning
confidence: 86%
“…36 In addition, adhesion to mature endothelial cells after activation with TNF-␣ was enhanced only in controls but not in patients with rheumatoid arthritis. 37 The functional activities of isolated EPCs, such as proliferative, migratory, adhesive, and in vitro vasculogenesis capacity, were also impaired in patients with hypercholesterolemia. 38 Finally, in SHR as well as in patients with essential hypertension endothelial function is impaired and may contribute to reduced vessel regeneration in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Like other cardiovascular risk factors, RA is associated with endothelial dysfunction (Herbrig, Haensel et al 2006). Patients with RA have a life expectancy that is reduced by 5-10 years and the excess mortality is from cardiovascular disease which is increased roughly 4-fold (Wrigley, Lip et al 2010).…”
Section: Inflammatory Conditionsmentioning
confidence: 99%
“…However, the patients with RA that are at particular cardiovascular risk are those with active disease and high disease activity scores (Grisar, Aletaha et al 2005). EPC numbers and EPC proliferative capacity show an inverse correlation with disease activity scores (Grisar, Aletaha et al 2005;Herbrig, Haensel et al 2006;Egan, Caporali et al 2008). The increased risk of cardiovascular events is not limited to RA and has been described in other inflammatory states such as systemic lupus erythematosus (SLE) (Urowitz, Bookman et al 1976;Roman, Shanker et al 2003), human immunodeficiency virus (HIV) infection (van Leuven, Sankatsing et al 2007), inflammatory bowel disease (Danese and Fiocchi 2003) or periodontitis (Mattila, Nieminen et al 1989).…”
Section: Inflammatory Conditionsmentioning
confidence: 99%